General practitioners’ deprescribing decisions in older adults with polypharmacy - Jungo, Katharina Tabea (2021)
Funding: The work of Katharina Tabea Jungo was supported by the Swiss National Science Foundation (SNSF) (NFP 407440_167465, PI Prof. Streit) and the work of Zsofia Rozsnyai by the Swiss Society of General Internal Medicine (SGAIM) Foundation (PI Prof. Streit). The SGAIM Foundation reviewed the study protocol but did not give us feedback or help usplan, conduct, interpret results, or write this manuscript. The SNSF had the same role but did not review the study protocol. CM is funded by the National Institute for Health Research (NIHR) Applied Research Collaborations (West Midlands), the NIHR School for Primary Caren Research and an NIHR Research Professorship in General Practice (RP 2014–04-026). The views expressed are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health and Social Care. ER is supported by an NHMRC-ARC Dementia Research Development Fellowship.